Students’ and Teachers’ Perception of Learning English for Young Learners - Saragi, Lusi Adelia Paskah; Yana, Dewi; Putri, Aulia; Edi, Warno (Fakultas Sastra - Universitas Muslim Indonesia, 2022)
During technological and scientific developments, young learners were supposed to be accustomed to the English language. Conversely, studies on how children and teachers view English for young learners seem still limited. Thus, this study aims to find out students' and teachers' perceptions of learning English for young learners. A qualitative descriptive was applied in this study and involved 33 students and 2 English teachers in SDS Cahaya Kasih Batam. An observation checklist, questionnaire, and interview were conducted to collect the data. The indicators which were applied in the instruments are cognitive, affective, behavioral, personality, interests, and expectation. The observation checklist was done to observe the classroom situation. Those questionnaires were distributed to the students and English teachers. The last data, students' and teachers' interviews were conducted to become additional and clarify the results obtained from the questionnaire. The outcome of this study highlighted that the students and English teachers positively perceived learning English for young learners. Teaching English at an early age for young learners helps them accustomed to English and capable to deal with science and technology development.